A New Approach for Management of Carious Premolars. “A Case Report" (Medical Forum Monthly, 2024)
With the main goals of retaining natural dentition and harmonic periodontal restorative interrelationship, a second premolar with deep distal caries was managed to expose sufficient tooth structure for further restorative treatment. Using BENEX atraumatic extraction system, the tooth was surgically extruded and stabilized at a required level for three months, followed by its final restoration. The case was followed up to 1 year after extrusion that showed a healthy soft and hard supportive tissues.